2019
DOI: 10.1002/jcp.28443
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of X‐linked inhibitor of apoptosis protein in solid tumors: A systematic review and meta‐analysis

Abstract: X‐linked inhibitor of apoptosis protein (XIAP) is aberrantly expressed in solid tumors. Considering conflicting data, we conducted this meta‐analysis to investigate its prognostic role. Electronic databases were searched to collect studies about associations between XIAP expressions and survival outcomes. Hazard ratio (HR), odds ratio (OR), and 95% confidence interval (CI) were utilized as effect size estimates. A total of 3,794 patients from 21 published studies were included. The results revealed that high X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Similar results have been published in hepatocellular carcinoma (Augello, et al, 2009) and gastric cancer (Shibata, et al, 2007). Recent systematic reviews conducted on studying the association between XIAP levels and cancer prognosis in patients with different cancers have suggested that increased XIAP levels correlate with unfavorable prognosis (Gao, et al, 2019;S. Li, et al, 2019) These studies indicate that the most widely studied IAPs: cIAP1 and 2 and XIAP are frequently overexpressed in a number of cancers and that their levels could help predict prognosis and clinical outcomes.…”
Section: Expression Of Iap Proteins In Cancer and Correlation With Prognosissupporting
confidence: 71%
“…Similar results have been published in hepatocellular carcinoma (Augello, et al, 2009) and gastric cancer (Shibata, et al, 2007). Recent systematic reviews conducted on studying the association between XIAP levels and cancer prognosis in patients with different cancers have suggested that increased XIAP levels correlate with unfavorable prognosis (Gao, et al, 2019;S. Li, et al, 2019) These studies indicate that the most widely studied IAPs: cIAP1 and 2 and XIAP are frequently overexpressed in a number of cancers and that their levels could help predict prognosis and clinical outcomes.…”
Section: Expression Of Iap Proteins In Cancer and Correlation With Prognosissupporting
confidence: 71%
“…XIAP acts as an anti-apoptotic protein via the inhibition of caspase-3 and caspase-7 activation, and high XIAP expression is associated with poor survival in several solid tumors. 15 , 16 Thus, the miR-200b-3p-mediated repression of XIAP mRNA expression appears as a mechanism governing the caspase-3 and caspase-7 activity and apoptosis. In theory, in the presence of miR-200b-3p, XIAP mRNA expression is repressed and caspase-3 and caspase-7 can be activated to promote apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies on XIAP (X-linked Inhibitor of apoptosis) as a target and prognostic biomarker in other cancer types. For example, use of XIAP BIR domain as a target for discovering antagonists [ 36 , 37 ]; the role of XIAP in mitochondrial membrane permeability as a target for cancer therapy [ 38 ]; and the prognostic value of XIAP in various cancer [ 39 , 40 ]. In contrast, the studies of XIAP in RCC are limited.…”
Section: Xiapmentioning
confidence: 99%